Peran Kiai Dalam Penguatan Karakter Religius Remaja (Jama’ah Musholla Ar-Rohman Desa Karangwage-Trangkil-Pati) - Nur Isro’ah (Jurnal Ilmiah Wahana Pendidikan, 2022)
The influence of globalization on youth is very strong. The influence of globalization has made many teenagers lose their personality as Indonesians. This is indicated by the symptoms that appear in everyday life. From how to dress, hairstyles that follow a lot of western culture. In addition, in the world of teenagers lately, there are also many news about the phenomena and problems that occur in teenagers today, such as the number of brawls between students, the habit of skipping school, drinking alcohol, smoking addiction, and not infrequently teenagers consuming drugs. This is where the important role of religious character education in anticipating moral degradation for adolescents. In character education, it is defined as an effort to educate children so that they can make wise decisions and practice them in daily life, so that they can make a positive contribution to their environment. which is applied in strengthening the religious character of adolescents in the village of Karangwage, Trangkil, Pati. In this study using a qualitative method based on a case study. Data collection techniques using observation, interviews and documentation. While the data analysis technique uses data reduction, data display and data verification.